La antropotecnología: un programa singular en la historia de las ciencias del trabajo - Yves Cohen (Universidade do Porto, 2012)
This paper is repositioning anthropotechnology in the history of work sciences. It defines this disciplinary field, through the singularities of its theoretical and practical postures. Between anthropology and ergonomics, anthropotechnology was carved over its various field work experiences, a particular space in the scientific and pragmatic horizon.